Louvação a Eunice : um estudo de analise da obras para piano de Eunice Katunda - Souza, Iracele Aparecida Vera Livero de, 1961- (2003)
Orientadores: Maria Lucia Senna Machado Pascoal, Mauricy Matos Martin,